A comparative study of the antibacterial properties of milk from different domestic animals. (6th January 2021) - Ebrahimi, Alireza; Moosavy, Mir‐Hassan; Khatibi, Seyed Amin; Barabadi, Zahra; Hajibemani, Abolfazl
Abstract : This study aimed to compare the antimicrobial properties of milk from donkey, horse, goat, sheep, cow and camel. The antibacterial properties of samples were analysed against foodborne pathogenic bacteria held at 5, 10 and 20 °C during 96 h of storage. The highest antimicrobial activity was obtained with donkey and horse milk at 20 °C after 96 h. This study has highlighted the variations in the antibacterial properties of the milk from various animal species. The extent of antibacterial activity of milk was shown to depend upon the animal species, the storage temperature and the bacterial strain studied. Abstract : Comparison of the antibacterial properties of milk from different domestic animals.